Direct Private Cost of Undergraduate Education in Southwest, Nigeria - Alabi, Festus Oluwole; Akinde, Temiloluwa Mabel (International Journal of Educational Management, 2021)
Individuals have always shown interest in monitoring the cost of their activities, in an educational institution, cost monitoring ensures that financial and other outlays of education could be justified by the number of clients being served and the quality of education provided. As a result of its important nature, cost received significant attention from scholars across discipline. This study therefore examined the private cost of undergraduate university education in south west, Nigeria. Descriptive research design of survey type and ex-post facto designs were adopted for the study. The population for the study consisted all final year undergraduates university students in South West Nigeria, Multi-stage sampling technique was used to select four universities from South West, Nigeria. A self-developed questionnaire titled private cost inventory questionnaire (PCIQ) was used to collect data. Two research questions were raised to guide the study and descriptive statistics of mean, bar charts, line graph and percentage were used to answer the research questions. Two hypotheses were formulated and inferential statistics like t-test and multiple regression were used to test the hypotheses at 0.05 level of significance. Findings revealed that there was significant difference between the direct private cost of university education in federal and state university. It revealed that there was significant difference in the direct private cost of undergraduate education among faculties in the same university. Also, findings revealed that the best predictor of direct private cost were feeding with 45.0%, accommodation with 11.4% and total school fees (receipted) with 10.5%. It was concluded that the private costs incurred by the students in the universities are high, especially in the state universities. Also, courses like Sciences and Law and Medicine are costly.It was recommended that there is need for the federal